Meningkatkan Keterampilan Writing of Narrative Text dengan Menggunakan Teaching Materials - Mardiyah; Mustaji; Nurmida Catherine Sitompul (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2019)
The teaching of writing Narrative Texts for middle school students is not easy because students have difficulty in composing sentences and expressing ideas in writing skills. The goal of this study is to find the effectiveness of the development of teaching materials. The development of teaching materials is using the Borg and Gall development model and a qualitative descriptive approach. The results of the review of the feasibility of product development as follows the review of English material experts by 90%, review of learning design experts by 95%. The results of this study indicate that the development of teaching materials gives better results than not using teaching materials. There was an increase in the score of learning outcomes by 45% for the experimental class. Furthemore,The control class also increased by 40%. Product trials for students and teachers through questionnaires received a very good response.